Ethnobotany of the construction of a traditional ceremonial house (Ù-sulë́) in a Bribri community of Talamanca, Costa Rica (UNED Research Journal, 2020)
Introduction: The Bribri are an Amerindian group from Costa Rica that has a traditional house, the Ù-sulë́, used for ceremonies led by the healer or Awá. This study was a shared experience about the Ù-sulë́, with inhabitants of the Bribri Indigenous Territory in the communities of Kácha’bli, Korbita and Amu’bli in Talamanca, Costa Rica. Objectives: To describe the construction of an Ù-sulë́, to observe and identify the plant species used throughout the process, to relate ethnobotanical information to cultural and historical aspects and to know some information about how this construction has changed in the past decades. Methods: Visits, meetings and interviews were organized in the aforementioned communities; all the stages of the construction were observed, and in a forest of the indigenous territory, specimens of the majority of plant species used in the process were collected and prepared. All the information for this study was provided by doctors (Awapa), older women, young people and indigenous Bribri professionals, who diligently collaborated to shape the study. Most plant species were identified by experienced curators from three Costa Rican herbaria (CR, JVR and USJ). Results: The complex construction process of an Ù-sulë́ is described in detail and for the first time the majority of plant species that are currently used to build this house were observed, collected and identified; amongst them Chloroleucon sp. (Fabaceae), Geonoma congesta and Iriartea deltoidea (both Arecaceae), Heteropsis oblongifolia (Araceae), three Miconia species (Melastomataceae), Minquartia guianensis (Olacaceae), and Pithecoctenium crucigerum (Bignoniaceae) are outstanding. Some species of plants used in the past were replaced because they had become scarce, or they were substituted against the ancestral wisdom (Sĩwã') in favor of a modern pragmatism related to criteria of sustainability. Discussion: The historical and cultural meaning of rescuing the almost lost tradition of Ù-sulë́, which in the past was built by volunteer workers with the Bribri mentality of "we help each other", is discussed, but nowadays it is an onerous work carried out with business mechanisms, influenced by the dominant Western culture. Thus, the monetization of this and other processes implies a risk for the traditional Bribri culture.
Keywords: useful plant species; Bribrí indigenous territory; Bribrí-Cabécar indigenous culture; original wisdom; Sĩwã´